The impact of diﬀerent exercise approaches on balance in people with pes planus - Demircioglu, Gamze; Genc, Hazal (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction. Pes planus is caused by the extension of the intrinsic muscles in the medial arch of the foot, resulting in the arch approaching the ground or the sole of the foot touching the ground completely. The objective was to determine how exercise techniques aﬀected patients with pes planus’ ability to balance and to recommend the appropriate exercises.Methods. In this study, 39 individuals with pes planus were allocated at random to either a stretching or stability and mobility exercise group. Star Excursion Balance Test, The Berg Balance Scale, The Functional Reach Test, and Weight Bearing Lunge, plantar ﬂexion range of motion (ROM) assessments were performed before treatment and after treatment for a total of four weeks.Results. The results demonstrated that both groups’ balance and ROM during intragroup testing had improved (p < 0.05). Only the improvement in plantar ﬂexion ROM in group 1 was found to be statistically higher than that in group 2 with group com-parisons (p < 0.05).Conclusions. Balance and ROM values were similarly aﬀected by both 4-week pes planus exercise programs. We contend that the static and dynamic foot kinematics were successfully rectiﬁed with both of our treatment techniques.
Keywords: ﬂatfoot; foot; postural balance; exercise therapy